MOVING TOWARDS DIGITALIZATION: UNVEILING CHALLENGES AND PROSPECTS OF E-MARKETING IN LEAST DEVELOPED ECONOMIES – THE CASE OF YEMEN - Sanad, Salah Naji Taher; AL-Shameri, Nawar A. S.; Al-Radai, Shaima Saleh Mohammed (International Journal of Research -GRANTHAALAYAH, 2023)
This study aims to shed light on the challenges and potential opportunities for e-marketing in developing economies with particular reference to Yemen. Secondary data from relevant reports, research papers, books, and other Internet resources is used in the study. The current study indicated that e-marketing in Yemen confronts several challenges, including poor communication infrastructure, lack of e-marketing knowledge, limited Internet and social media users, an unstable power supply, lack of trust, and lack of government incentives. However, there are prospects for e-marketing to thrive in Yemen, such as the growing youthful population, the rise in mobile phone users, and the introduction of 4G technology. The study suggests investing in infrastructure, increasing digital literacy, resolving security concerns, and active collaboration among businesses, government entities, and other stakeholders. Implementing these suggestions can improve e-marketing effectiveness and contribute to the country’s economic growth.